Cultural perceptions of ethical leadership and its effect on intention to leave in the independent hotel industry. Issue 1 (23rd November 2021) - Nazarian, Alireza; Zaeri, Ehsan; Foroudi, Pantea; Afrouzi, Amir Reza; Atkinson, Peter
Abstract : Purpose: Studies have shown that due to the high direct and indirect costs of staff turnover, there is a need for managers to use approaches that engender a feeling that the organisation is fair to its employees and consequently reduce the intention to leave. However, to understand how to apply the research findings and theories from different parts of the world, we need to understand how employees' perceptions of such factors as ethical leadership and organisational justice are affected by the national culture. Therefore, this study aims to compare the impact of ethical leadership on the intention to leave through justice, loyalty and satisfaction among employees of independent hotels from two Global Leadership and Organizational Behaviour Effectiveness (GLOBE) cultural clusters. Design/methodology/approach: A total of 1, 561 questionnaires were received from independent hotel employees, which were analysed using structural equation modelling. Data were collected in the USA, the UK, Italy and Spain whose national cultures fall into two different GLOBE regional clusters. Findings: The results show similarities and differences between countries and within and between clusters. No relationship was found between procedural justice and intention to leave in any of the four countries. Ethical leadership had no significant impact on job satisfaction and organisational justice in the UK, which contrasts with results in the other three countries. The study findings also show that distributive justice has a significant relationship with the intention to leave in the USA and the UK (Anglo cluster), whereas no specific relationship was found between these two variables in Italy and Spain (Latin European cluster). Originality/value: This study contributes to the literature of ethical leadership and its application to the hotel industry in two culturally different GLOBE clusters. This study shows how the relationships between organisational variables are affected by national culture and emphasises the importance for hotel managers of being aware of the specific characteristics of the culture of the country in which they are operating.